Transversal strength of heat-cured acrylic resin after immersion in Annona muricata L. effervescent extract - Kusumawardani, Chaterina Diyah Nanik; Razak, Arifzan; Ariestania, Vivin; Lubis, Raysha Teres (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Heat-cured acrylic resin is one of the most widely used denture bases. Patients need to keep the removable dentures clean in order for them to have no adverse impacts. Natural ingredients, such as Anonna muricata L., are known for their benefits and can be used as a denture cleanser, but their effect towards mechanical properties needs to be studied. The objective of this study is to analyze the role of Anonna muricata L. effervescent extract with various concentrations (25, 35, and 45%) on the transversal strength of heat-cured acrylic resin. Methods: The samples were twenty eight heat-cured acrylic resin plates with a size of 65x10x2.5 mm randomly divided into four groups. The control group (immersed in distilled water), the 25, 35, and 45%, were immersed for fifteen minutes three times a day for ten days. The transversal strength was measured by the Universal Testing Machine (Shimadzu) loaded at 1kN with a constant control rate of 1 mm/min and analyzed by Kruskal-Wallis. Results: The average transversal strength of the control group was 118.59 MPa, followed by 25% with 114.35 MPa, 35% with 117.28 MPa, and 45% with 111.32 MPa. Based on Kruskal-Wallis, there were no significant differences with a significant value p>0.05 (p=0.886). Conclusion: The immersion of heat-cured acrylic resin in the extract of Anonna muricata L. effervescent does not affect the transversal strength of the material.